2020
DOI: 10.1002/jum.15255
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Quantitative Quality Measurements of the Urethral Rhabdosphincter Muscle by Supersonic Shear Wave Imaging in Women With Stress Urinary Incontinence

Abstract: ObjectivesTo quantitatively assess the quality of the urethral rhabdosphincter muscle by measuring its shear wave velocity (Vs) and calculating the Young modulus (E) with supersonic shear wave imaging (SSI).MethodsThis was a prospective study of 43 women with SUI and 52 female control participants who underwent a transperineal US examination with SSI. Supersonic shear wave imaging was performed at rest with a linear transducer and a specialized‐preset procedure. The stability and validity of the shear waves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…SUI correlates with the loss of closing pressure, which appears to be related to rhabdosphincter muscle mass 18 . The stiffness of the rhabdosphincter increases with increasing urethral sphincter quality 5,19 . In this study, we indirectly evaluated the biological properties of the rhabdosphincter to reflect the urethral closing pressure and rhabdosphincter contractility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SUI correlates with the loss of closing pressure, which appears to be related to rhabdosphincter muscle mass 18 . The stiffness of the rhabdosphincter increases with increasing urethral sphincter quality 5,19 . In this study, we indirectly evaluated the biological properties of the rhabdosphincter to reflect the urethral closing pressure and rhabdosphincter contractility.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this study is the collection of SWE measurements at the anterior and posterior rhabdosphincter, which is superior to previous studies in which the anterior rhabdosphincter alone was the research object 5 . Unexpectedly, we found that the thickness and stiffness measurements of the anterior rhabdosphincter were generally larger than those of the posterior rhabdosphincter, perhaps because there are significant differences in the closing pressure of the four walls of the urethra, with the anterior urethral wall having the highest closing pressure and the posterior wall having the lowest pressure 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao B used supersonic shear wave imaging to compare the stiffness of the striated urinary sphincter in women with stress incontinence. Comparing 40 patients with stress urinary incontinence and 40 healthy subjects with no difference in age, as well as the body mass index and parity between the groups, they observed that the stiffness of the urethral rhabdosphincter muscle was significantly lower in women with stress urinary incontinence (mean values: 2.54 vs. 2.73 m/s; 19.7 vs. 22.7 kPa) [ 90 ].…”
Section: 4 Urethramentioning
confidence: 99%